Indacenodithienothiophene-Based Ternary Organic Solar Cells - Gasparini, Nicola; García-Rodríguez, Amaranda; Prosa, Mario; Bayseç, Şebnem; Palma-Cando, Alex; Katsouras, Athanasios; Avgeropoulos, Apostolos; Pagona, Georgia; Gregoriou, Vasilis G.; Chochos, Christos L.; Allard, Sybille; Scherf, Ulrich; et al. (Frontiers in Energy Research, 2017)
One of the key aspects to achieve high efficiency in ternary bulk-hetorojunction solar cells is the physical and chemical compatibility between the donor materials. Here, we report the synthesis of a novel conjugated polymer (P1) containing alternating pyridyl[2,1,3]thiadiazole between two different donor fragments, dithienosilole and indacenodithienothiophene (IDTT), used as a sensitizer in a host system of indacenodithieno[3,2-b]thiophene,2,3-bis(3-(octyloxy)phenyl)quinoxaline (PIDTTQ) and [6,6]-phenyl C70 butyric acid methyl ester (PC71BM). We found that the use of the same IDTT unit in the host and guest materials does not lead to significant changes in the morphology of the ternary blend compared to the host binary. With the complementary use of optoelectronic characterizations, we found that the ternary cells suffer from a lower mobility-lifetime (μτ) product, adversely impacting the fill factor. However, the significant light harvesting in the near infrared region improvement, compensating the transport losses, results in an overall power conversion efficiency enhancement of 7% for ternary blends as compared to the PIDTTQ:PC71BM devices.